2016
DOI: 10.1074/jbc.m115.688143
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Mechanism of the ζ Subunit of the F1FO-ATPase Nanomotor of Paracoccus denitrificans and Related α-Proteobacteria

Abstract: The subunit is a novel inhibitor of the F 1 F O -ATPase of Paracoccus denitrificans and related ␣-proteobacteria. It is different from the bacterial (⑀) and mitochondrial (IF 1 ) inhibitors. The N terminus of blocks rotation of the ␥ subunit of the F 1 -ATPase of P. denitrificans (Zarco-Zavala, M., Morales-Ríos, E., Mendoza-Hernández, G., Ramírez-Silva, L., Pérez-Hernández, G., and García-Trejo, J. J. (2014) FASEB J. 24, 599 -608) by a hitherto unknown quaternary structure that was first modeled here by struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…The biochemical work of García-Trejo and co-workers [ 29 , 30 , 36 ], together with the structure of P. denitrificans ATP synthase that revealed the ζ subunit bound in a manner analogous to the eukaryotic inhibitor protein IF 1 [ 13 ], indicated that the ζ subunit is responsible for preventing ATP hydrolysis and enforcing unidirectional catalysis in the P. denitrificans enzyme. However, deleting the ζ subunit caused only very moderate increases in ATP hydrolysis (less than twofold), and the rates remain very low in comparison with the rates observed from the mammalian and E. coli enzymes ( table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical work of García-Trejo and co-workers [ 29 , 30 , 36 ], together with the structure of P. denitrificans ATP synthase that revealed the ζ subunit bound in a manner analogous to the eukaryotic inhibitor protein IF 1 [ 13 ], indicated that the ζ subunit is responsible for preventing ATP hydrolysis and enforcing unidirectional catalysis in the P. denitrificans enzyme. However, deleting the ζ subunit caused only very moderate increases in ATP hydrolysis (less than twofold), and the rates remain very low in comparison with the rates observed from the mammalian and E. coli enzymes ( table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the sequence of its inhibitory region is weakly related to that of the mitochondrial inhibitor IF 1 (32). Biochemical and crystallographic evidence supports the notion that the ζ-inhibitory mechanism resembles that of IF 1 , in which the ζ-intrinsically disordered inhibitory domain adopts a helical structure after occupying its inhibitory position in the α D β D -catalytic interface of its cognate F 1 , equivalent to IF 1 (26,33).…”
mentioning
confidence: 81%
“…Latency of ATP hydrolysis activity of the mycobacterial F‐ATP synthase has also been observed for the thermoalkaliphilic Ct F 1 ‐ATPase [39,40] and the α‐proteobacterium Paracoccus denitrificans F‐ATP synthase [41,42]. Based on the Ct F 1 ‐ATPase crystallographic structure, the hydrolytic bound product of ADP and Pi within the β E ‐catalytic site was described to be likely the basis of inhibition of ATP hydrolysis of this enzyme [39].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Ct F 1 ‐ATPase crystallographic structure, the hydrolytic bound product of ADP and Pi within the β E ‐catalytic site was described to be likely the basis of inhibition of ATP hydrolysis of this enzyme [39]. In comparison, besides subunit ε the P. denitrificans F‐ATP synthase contains an additional subunit called ζ, which is different in structure from the bacterial ε and mitochondrial inhibitor protein, IF 1 [41]. ζ harbours the N‐terminal inhibitory domain and a globular anchoring domain.…”
Section: Resultsmentioning
confidence: 99%